Echocardiography. Issue 6656 (29th October 1988) - Chambers, J. B.; Monaghan, M. J.; Jackson, G.
Abstract : Imaging echocardiography is an important extension of the clinical examination and will answer most questions in an emergency-for example, whether an enlarged cardiac shadow on the chest radiograph represents ventricular dilatation or an effusion. Doppler ultrasonography is essential for hospitals with an interest in cardiology because it provides direct haemodynamic data that are complementary to imaging. It requires more skill than imaging and may also be time consuming. Colour flow Doppler mapping is speedy and simple to use and aids the interpretation of continuous wave Doppler. It is therefore a natural companion to conventional Doppler, but there would have to be a high clinical load to justify its purchase.